Implementasi Kurikulum MBKM (Merdeka Belajar Kampus Merdeka) Dalam Meningkatkan Kualitas Pendidikan di Indonesia - Nizar Nizar; Reo Tomi Pratama; Mustafiyanti Mustafiyanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The independent curriculum is a new curriculum implemented by the ministry of education and culture as an effort to improve educational conditions after Covid-19. Curriculum change is a natural and natural process should happen as stated by Oliva (2004)